A dança e a crítica: Uma análise de suas relações na cidade de São Paulo - Oliveira, Flávia Fontes (2007)
The project at hand examines two of the most relevant moments of the Brazilian art of dancing as seen through its reflexes in the media. To attain this objective, we analyzed the corpus constituted by reviews published on the subject of dancing in the two most important daily newspapers of the largest city in the country: São Paulo Folha de São Paulo and O Estado de São Paulo, between the periods of 1975-1980 and 1995-2000. Our survey presents an overview of essential elements in search of connection between art and media in the Brazilian contemporary culture. Our secondary objetive was to focus on responses of the performance of critics. As far as methodology is concerned, our study is based on texts written by authors Flora Sussekind, Adorno, Gerd Borheim, Roberto Schwartz, Davi Arrigucci Jr. among others, proceeding to in-depth analysis of each professional criticism and the general panorama. This study also shows the reflection of time in the art of dancing, as picture of an entire generation, as opposed to only one author. At the same this paper will present a record of the major dancing events in São Paulo, within the periods stated above, as seen through the particular political and economic moment in time of the country. Consequently, perspectives appoint towards the conclusion that reviews and professional criticism of dancing became more relevant with the increase of performances in this art form, as São Paulo turned into the cultural center of the country in the last few decades. There is no way to deny the dialogue between dance and criticism, although not necessarily to the extent suggested by the theories which had been examined. However, definitely, there is a conjunction betwen the art of dancing and professional criticism